Implementation of 3D printed superior mesenteric vascular models for surgical planning and/or navigation in right colectomy with extended D3 mesenterectomy: comparison of virtual and physical models to the anatomy found at surgery - Luzon, Javier A.; Andersen, Bjarte T.; Stimec, Bojan V.; Fasel, Jean H. D.; Bakka, Arne O.; Kazaryan, Airazat M.; Ignjatovic, Dejan (Surgical endoscopy, 2019)
Background Three-dimensional (3D) printing technology has recently been well approved as an emerging technology in various fields of medical education and practice; e.g., there are numerous studies evaluating 3D printouts of solid organs. Complex surgery such as extended mesenterectomy imposes a need to analyze also the accuracy of 3D printouts of more mobile and complex structures like the diversity of vascular arborization within the central mesentery. The objective of this study was to evaluate the linear dimensional anatomy landmark differences of the superior mesenteric artery and vein between (1) 3D virtual models, (2) 3D printouts, and (3) peroperative measurements. Methods The study included 22 patients from the ongoing prospective multicenter trial “Safe Radical D3 Right Hemicolectomy for Cancer through Preoperative Biphasic MDCT Angiography,” with preoperative CT and peroperative measurements. The patients were operated in Norway between January 2016 and 2017. Their CT datasets underwent 3D volume rendering and segmentation, and the virtual 3D model produced was then exported for stereolithography 3D printing. Results Four parameters were measured: distance between the origins of the ileocolic and the middle colic artery, distance between the termination of the gastrocolic trunk and the ileocolic vein, and the calibers of the middle colic and ileocolic arteries. The inter-arterial distance has proven a strong correlation between all the three modalities implied (Pearson’s coefficient 0.968, 0.956, 0.779, respectively), while inter-venous distances showed a weak correlation between peroperative measurements and both virtual and physical models. Conclusion This study showed acceptable dimensional inter-arterial correlations between 3D printed models, 3D virtual models and authentic soft tissue anatomy of the central mesenteric vessels, and weaker inter-venous correlations between all the models, reflecting the highly variable nature of veins in situ.